Religious institutions and measure to prevent crime in the Islamic jurisprudence - Ibrahim Mohamed, Hossam El Din (s.n, 2012)
A lot of people are enjoying the services of a wide range of religious institution, especially in the modern era. While these institutions care for the spiritual aspects of individuals and groups in Western countries, in the Muslim world religious institutions are covering different areas including supervising spiritual and religious life, solving problem of society through social solidarity of Alms committees and charities, organizing social and political relations, arbitrary crime solving, trade and commodities and many more. In additional to the above, scholars are playing an important advisory role in supervising the reform which is taking place within the Islamic institutions in order to achieve the main objectives of Shari'ah which intend to bringing happiness to Muslims and the human kind as whole. This research intends to focus on the role played by these institutions in curbing crime and expose the different measures taken for this purpose